Debromination of tetrabromobisphenol A in aqueous amine solutions under hydrothermal conditions. (December 2020) - Sakabe, Junichi; Kimura, Yuta; Endo, Jun; Funazukuri, Toshitaka
Highlights: The yield of bromide ion from TBBPA reached 89% at 533 K for 20 min. Aqueous amine solutions were highly effective for debromination of TBBPA. The rates increased with increasing methylamine concentration and reaction temperature. The activation energy above 473 K was much lower than that in pyrolysis. A debromination pathway of TBBPA in aqueous amine solution was proposed. Abstract: Tetrabromobisphenol A (TBBPA) powder was subjected to an aqueous amine solution in a small bomb-type batch reactor at temperatures from 447 to 553 K and pressures from 0.79 to 6.4 MPa. The effectiveness of aqueous amine solutions under hydrothermal conditions was examined for debromination of TBBPA, which is a brominated flame retardant commonly contained in printed circuit boards. The amines tested were methylamine, dimethylamine and trimethylamine. Compared to aqueous ammonia and aqueous sodium hydroxide solutions, all the amine solutions tested were more effective. For instance, the 89% debromination of the initial bromine contained in TBBPA was recovered by a 0.6 mol/kg aqueous methylamine solution at 533 K in 20 min. The debromination of TBBPA was accelerated with increasing reaction temperature and amine concentration. The four major products, 2, 6-dibromophenol, 2-bromophenol, phenol and 2, 6-dibromo-4-(1-methylethenyl)phenol, were detected by GCMS and the three former products were quantified by HPLC. According to the product distributions over time, a primary pathway of TBBPA debromination was proposed, in which the cleavage of a carbon-carbon bond initially took place, followed by debromination. The debromination reaction in an aqueous methylamine solution under hydrothermal conditions was described by pseudo first order reaction kinetics, and the activation energies changed at 473 K, and that above 473 K was much smaller than that in pyrolysis reported in the literature. The debromination rate constants at 473 and 533 K were proportional to methylamine concentration up to 0.3 mol kg −1, and those increased gradually above the temperature. The authors proposed debromination of TBBPA in an aqueous amine solution under hydrothermal conditions as a new debromination method due to relatively fast reaction rates and recovery of bromine as bromide ion.